Intraoperative Germinoma Staining: A Technical Note - Naydenov, Emanuil; Karazapryanov, Petar; Pavlov, Velislav; Metodiev, Dimitar; Minkin, Krasimir (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
As the main treatment modality of central neural system germinomas is radiotherapy and/or chemotherapy, the exact initial diagnosis of the disease is crucial. Depending on the different national protocols, histologic verification can be obligatory in some instances. This is a serious challenge, taking into account the usual location and nonspecific macroscopic appearance of these lesions. Here, we propose a safe and effective method of intraoperative tumor enhancement that can increase the confidence of the surgeon during the intervention.
Keywords: germinoma; intraoperative enhancement; fluorescein sodium